A war of nerves : soldiers and psychiatrists in the twentieth century - Shephard, Ben (Cambridge, Mass. : Harvard University Press, 2000)
"A War of Nerves" is the latest and most proficient of several accounts to survey the course of military psychiatry through the twentieth century. Shephard states that his purpose is to explore the psychological problems soldiers developed in the World Wars and during and after Vietnam, as well as the steps doctors took to counter them. In practice, the author thinks the patient's perspective impossible to recover; he therefore excavates selectively, concentrating more on the doctors' enforced negotiation of bureaucracies, and their attempted implementation of therapies. Spanning as he does the whole of the twentieth century from the pre-First World War period to the mid-1990s, Shephard lives up to his promise of a comprehensive and even-handed account which mainly considers the work of British medics in the two World Wars, but also bringing in European and American instances and the relatively less devastating conflicts in the second half of the century. The book is the most authoritative general account of twentieth century war psychiatry yet to emerge; both specialists and students will be well served its comprehensive, detailed coverage and by its humane, pragmatic approach.
Bibliografija: str. 469-473
Keywords: vojna psihologija; vijetnamski sindrom